2000
DOI: 10.1007/s004170050352
|View full text |Cite
|
Sign up to set email alerts
|

Transpupillar laser phototherapy for retinal and choroidal tumors: A rational approach

Abstract: Photothermotherapy is not without risk unless the temperature field can be well adapted to the tumorous structure, as temperature elevations outside a small therapeutic range that affect vital structures are considered to be a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 108 publications
(149 reference statements)
0
7
0
1
Order By: Relevance
“…Não foi considerada a ação focalizadora do cristalino; m) Uma condição de contorno de temperatura constante foi imposta para a superfície posterior da esclera; n) Uma condição de contorno convectiva foi imposta sobre a superfície anterior do olho com coeficiente de transferência de calor estimado por Lagendijk (Scott, 1988) considerando a evaporação do filme lacrimal e a troca de calor por radiação e convecção para o ambiente com h = (20 ± 2) W/m 2 °C; o) As temperaturas iniciais nas diferentes regiões do olho foram obtidas por meio de uma simulação preliminar em regime estacionário para o olho não exposto à radiação; e p) Os eixos pupilar, visual e óptico foram considerados como coincidentes devido à simetria do problema. Para determinar o valor do dano térmico causado ao tecido nas várias camadas do olho, será utilizado o modelo que Birngruber (Rol et al, 2000) desenvolveu para determinar a função dano na retina e na coroide durante tratamentos com termoterapia transpupilar a laser. O modelo descreve o efeito do calor na taxa de reação química, e considera a variação na concentração de moléculas não danificadas, utilizando a lei de Arrhenius.…”
Section: Nomenclaturaunclassified
“…Não foi considerada a ação focalizadora do cristalino; m) Uma condição de contorno de temperatura constante foi imposta para a superfície posterior da esclera; n) Uma condição de contorno convectiva foi imposta sobre a superfície anterior do olho com coeficiente de transferência de calor estimado por Lagendijk (Scott, 1988) considerando a evaporação do filme lacrimal e a troca de calor por radiação e convecção para o ambiente com h = (20 ± 2) W/m 2 °C; o) As temperaturas iniciais nas diferentes regiões do olho foram obtidas por meio de uma simulação preliminar em regime estacionário para o olho não exposto à radiação; e p) Os eixos pupilar, visual e óptico foram considerados como coincidentes devido à simetria do problema. Para determinar o valor do dano térmico causado ao tecido nas várias camadas do olho, será utilizado o modelo que Birngruber (Rol et al, 2000) desenvolveu para determinar a função dano na retina e na coroide durante tratamentos com termoterapia transpupilar a laser. O modelo descreve o efeito do calor na taxa de reação química, e considera a variação na concentração de moléculas não danificadas, utilizando a lei de Arrhenius.…”
Section: Nomenclaturaunclassified
“…The kinetics of the thermal denaturation, whose ABCM parameters are the activation energy and temperature, is represented by an integral damage, ΩD, that measures the produced physical damage. For a given damage, the denaturation is determined only by the temporal changes in tissue temperature (Rol et al, 2000).…”
Section: Physical-mathematical Modelmentioning
confidence: 99%
“…The heat generated by the electronic sensors can damage the adjacent neuronal tissue to the implant sites and also the implant. Furthermore, the increase in temperatures may foster an environment suitable to bacteria proliferation that could potentiate infections (Schwiebert et al, 2002). Energy dissipation and temperatures must be carefully controlled in order to avoid damage to the retina and adjacent tissues which in turn could disturb retinal capillary blood flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocoagulation of tissue occurs when light energy is transformed into thermal energy [5]. The argon lasers are used in a variety of ophthalmic surgeries (e.g., removal of conjunctival cysts, iridotomy, and trabeculoplasty) due to its convenience, effectiveness, and safety [6][7][8][9]. Also, Wohlrab et al [10] reported cases in which benign tumors of the eyelid were successfully removed with an argon laser.…”
Section: Introductionmentioning
confidence: 99%